超音波診断装置、超音波診断装置の制御プログラム、及び、超音波診断装置の制御方法 (2024)
To provide an ultrasonic diagnostic apparatus, when an ultrasonic image is displayed and output, capable of improving followability to a tissue structure with movement, while effectively removing noise.SOLUTION: An ultrasonic diagnostic apparatus includes a signal processing section 3 for sequentially generating frame data constituting an ultrasonic image of the inside of a subject, and a frame averaging section 4 of performing weighted addition of second frame data Do and first frame data Dn to generate output frame data Qn of an object to be displayed and output at a next time. The frame averaging section 4 performs weighted addition of the second frame data Do and the first frame data Dn in such a manner as to perform different weighted additions for every spatial frequency band of a tissue structure, where in the frame averaging section 4, the weight of the first frame data Dn setup to a tissue structure with low space frequency is larger than the weight of the first frame data Dn set up to a tissue structure with high space frequency.SELECTED DRAWING: Figure 2